Groups process and practice - Corey, Marianne Schneider 1942-; Corey, Gerald; Corey, Cindy (Brooks/Cole, Cengage Learning, 2014)
"This book outlines the basic issues and key concepts of group process and shows how group leaders can apply these concepts in working with a variety of groups. In many ways this is a 'how-to' book, but it is also a book about the 'why' of group leadership... For the ninth edition, each chapter has been carefully reviewed and updated to present the current thinking and trends in practice." --p. xxi